097 Transcranial sonography in the prodromal phase of PD. Issue 9 (12th August 2022) - Rees, Richard; Simonet, Cristina; Gill, Aneet; Giovannoni, Gavin; Lees, Andrew; Bestwick, Jonathan; Noyce, Alastair J; Schrag, Anette
Abstract : Introduction: Transcranial sonography (TCS) has been shown to be a reliable imaging biomarker in patients with Parkinson's disease (PD). 90% of patients with PD have enlarged nigral hyperechogenicity (SN+) compared to 10% healthy controls (HC). Objective: To assess the relationship between SN+ and motor and non-motor features of prodromal PD. Methods: Higher-risk (HR) and lower-risk (LR) age- and gender-matched controls from the PREDICT-PD study were compared alongside PD patients. TCS was performed with a cut-off of 0.20cm2 for SN+. Validated scales were used to assess motor and non-motor features. All assessments were undertaken blind to risk of PD determined by the PREDICT-PD algorithm. PREDICT-PD participants were compared according to enlarged or normal SN echogenicity. Results: 47 PREDICT-PD participants and 13 PD patients were compared. 40/47 PREDICT-PD participants and 12/13 PD patients had good quality sonographic appearances on at least one side. 24 PREDICT-PD participants had enlarged SN+ and 23 were normal. SN+ participants had higher MDS-UPDRS III scores than those with normal SN (mean 6 vs 4, p=0.036), but did not differ in any other domain. There was no relationship between SN+ and risk of PD. Conclusion: Despite evidence for use around the time of PD diagnosis in individuals with motor features of PD, we found no convincing evidence to support the use of TCS in the prodromal phase.